2013
DOI: 10.1111/jan.12262
|View full text |Cite
|
Sign up to set email alerts
|

The development of leadership outcome‐indicators evaluating the contribution of clinical specialists and advanced practitioners to health care: a secondary analysis

Abstract: Aims To report a secondary analysis of data collected from the case study phase of a national study of advanced practitioners and to develop leadership outcome‐indicators appropriate for advanced practitioners. Background In many countries, advanced practitioners in nursing and midwifery have responsibility as leaders for health care development, but without having leadership outcome measures available they are unable to demonstrate the results of their activities. In Ireland, a sequential mixed method researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 13 publications
4
54
0
Order By: Relevance
“…An exception is a large case study, conducted in 13 sites across Ireland and involving 23 Clinical Nurse Specialists and Advanced Practitioners (Clinical Midwife Specialists and Advanced Nurse Practitioners). An important finding of this study was the identification of multiple activities that focused on two areas of leadership; clinical and professional (Begley et al., ; Elliot, Begley, Kleinpell, & Higgins, ; Elliot et al., ). Clinical leadership activities supported the development of nursing practice in clinical settings or services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exception is a large case study, conducted in 13 sites across Ireland and involving 23 Clinical Nurse Specialists and Advanced Practitioners (Clinical Midwife Specialists and Advanced Nurse Practitioners). An important finding of this study was the identification of multiple activities that focused on two areas of leadership; clinical and professional (Begley et al., ; Elliot, Begley, Kleinpell, & Higgins, ; Elliot et al., ). Clinical leadership activities supported the development of nursing practice in clinical settings or services.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical leadership activities supported the development of nursing practice in clinical settings or services. Professional leadership activities supported the development of nursing practice outside the service at the national or international level (Elliot et al., , p. 1039).…”
Section: Introductionmentioning
confidence: 99%
“…Although research is part of the regulatory requirement for NPs in both Ireland and Australia, little research is available on this aspect of the role. The leadership role has been researched in Ireland, but no research has been found pertaining to leadership in Australian NPs (Elliott et al, , , ). There is no research to date comparing NPs leadership activities across two countries, or indeed ascertaining if NPs identify themselves as leaders of the nursing profession.…”
Section: Introductionmentioning
confidence: 99%
“…Organisations must explore innovative models of care that enhance care continuity. Advanced practice nurse roles have clearly demonstrated enriched staff knowledge and enhanced attitudes and tone of care 5. Furthermore, Acorn6 reported enhanced care continuity and satisfaction with an autonomous nurse practitioner as most responsible provider model for seniors admitted to a community hospital.…”
Section: Commentarymentioning
confidence: 99%